Pengaruh Faktor Makroekonomi Terhadap Resiko Pembiayaan Bank Syariah Studi Pada Bank Umum Syariah di Indonesia Tahun 2015-2018 - Rizki Fitriansyah Fitriansyah (Faculty of Economics and Management, 2019)
Sharia banks are one of the financial institutions that are currently still developing in Indonesia. The presence of sharia banks aim to become an alternative financial institution for people who need banking services using a profit sharing system. Like other financial institutions, Sharia banks also have a risk faced, namely the risk of financing. The risk of financing in Sharia banks is commonlyknown as the risk of impaired financing. The level of impaired financing in Islamic banks is one indicator of the level of the soundness of banks. The size of the impaired financing level is partly due to bad financing and the sluggishness of the real sector in response to macroeconomic conditions. The current economic conditions that have become macroeconomic concerns of the public include theinstability of exchange rates and inflation. Financial system instability (financial crisis) in addition to influencing banking liquidity also encouraged an increase in impaired financing for sharia banks. Based on the background above, this research conducted to determine the effect of macroeconomic factors, exchange, and comparison, on interest rates on Sharia Commercial Banks in Indonesia. The data used in this study are secondary data obtained from Sharia Banking Statistics (SPS) issued by the FinancialServices Authority (OJK) and economics statistical data from the Indonesian Bank. Analytical technic on this study uses multiple linear regression analysis techniques. The results shows that the rupiah exchange rate and the exchange rate were significant for impaired financing on Sharia Commercial Banks in Indonesia. Meanwhile, the exchange rate has a significant negative effect on impaired financing at Sharia Commercial Banks, while the exchange rate is significant against impaired financing at Sharia Commercial Banks